KEPEMIMPINAN KYAI DALAM PENGEMBANGAN ORGANISASI EKONOMI DI PONDOK PESANTREN - Supriyanto Supriyanto (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
This research aimed to explore the role of Kyai leadership in the development of cooperative organizations at pesantren therefore the contributions of Kyai can be seen on economic institute in pesantren. This study used a case study design with models of multisite study at two pesantren in Sidogiri Pasuruan and Minhajut Thullab Banyuwangi. The units of analysis of this study weic are Kyai, Teacher or Ustadz, the pesantren cooperative, students, the community around the pesantrens and members of the pesantren cooperative. Methods of data collection were indepth interviews, observation and analysis of the contents of the documentation. This study used qualitative design with a model of multisite case study technique. The data analysis and testing the validity of the data using the technique of triangulation, the source triangulation, methods triangulation and time triangulation. The findings of this study indicated that the leadership of Kyai played an important role in the management of pesantrens economic empowerment.